Systemic Factors Associated with Treatment Response in Diabetic Macular Edema. (23rd March 2020) - Wong, Wendy Meihua; Chee, Caroline; Bhargava, Mayuri; Chai, Charmaine; Lin, Hazel; Zhao, Paul; Ariadarma Mangunkusumo, Erlangga; Naing, Thet; Yuen, Yew Sen; Wong, Tien Yin; Su, Xinyi; Lingam, Gopal
Abstract : Purpose . To identify systemic factors that may influence the response to anti-VEGF therapy in patients with diabetic macular edema (DME). Methods . 35 patients undergoing anti-VEGF injections for centre-involving DME were studied in this prospective observational study. The primary outcome was change in macular thickness one month after treatment, measured using spectral-domain optical coherence tomography (OCT). At baseline, information on various systemic factors was collected including glycosylated hemoglobin (HbA1c), serum VEGF levels, lipid profile and markers of renal function, and blood pressure. Thirty-three of the 35 patients were included in this study. Nonparametric statistical tests were used for the analysis of the data in view of the nonnormal distribution of the outcome variables. Multivariate analysis was performed using logistic regression. Stata 12.1 software was used for the analysis. Main Outcome Measures . Reduction in macular central subfield thickness (on spectral-domain OCT) and change in logMAR visual acuity at one month after injection. Results . Lower HbA1c levels (7% or less) were significantly associated with greater reduction in central macular subfield thickness at one month after injection of bevacizumab or ranibizumab on both univariate analysis (p = 0.012 ) and multivariate analysis (p = 0.042 ). Conclusions . Better glycemic control is associated with a greater reduction in central macular thickness after the first injection of bevacizumab or ranibizumab in diabetic macular edema. Patients with high levels of HbA1c and poor response to anti-VEGF may benefit from strict control of their blood glucose.